Akhlak Guru Terhadap Murid Di Era Masa Kini Menurut Imam Ghazali - Aida Efendi; Carina Septiani; Saidah Syakira; Zahra Dalvinova; Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Every teacher has an obligation to educate their students to become intelligent children with noble character based on the Koran. This research aims to describe and analyze the morals of teachers towards students in the educational process in the current era, according to Imam Ghazali's point of view in the book Ihya' Ulumuddin, teaching is a noble profession so that people who become teachers are imitated by everyone, and teachers must have Ethics towards students: Show affection towards students, and treat them like their own children. Teachers must not ask for favors or rewards from their students. The method used in this research is a descriptive qualitative method with a Library Research approach. This method uses books, magazines and journal articles as the main reading sources, the main data sources come from written articles contained in books, magazines and articles related to the theme of this research. The results of this research show that teacher morals towards students are very necessary. A teacher is a person who provides benefits for students in reaching the essence of human creation, namely the afterlife. So teachers must always teach good things to their students, because their students will always put them into practice.